Current Trends, Spatio‐Temporal Dynamics of Microplastics Research and Global Public Health: A Scientometric Study - Juan Alvitez; Luis Huarachi; Abigail Temoche; Carlos Medina; Daniel Alvitez‐Temoche; Miguel Cabanillas‐Lazo; Frank Mayta‐Tovalino (Health Science Reports)
ABSTRACT Purpose To evaluate the current trends and spatiotemporal dynamics of microplastic research and public health through a scientometric study from 2019 to 2024. Methods An observational and descriptive approach was applied to the published literature on microplastics and public health published in January 2019 and July 2024. A quantitative approach was used to analyze document production, author–country collaborations and thematic evolution. A comprehensive search of the Scopus database was conducted using a combination of keywords related to “microplastics” and “public health.” Papers that explicitly addressed these topics were considered for analysis. SciVal and R studio software were used for the analyses. Results Significant growth in paper production was observed, with an increase in international collaboration and a diversity of paper types. The most prominent journals in this field include “Science of the Total Environment” and “Journal of Hazardous Materials”, which lead in terms of academic output and impact. There was an upward trend in the number of publications in the Q1 quartile, reflecting growing interest in this field. Several authors have demonstrated a significant impact on microplastic research and its impact on public health, highlighting the importance of further research in this field. In addition, 156 sources and 259 papers related to microplastics and public health research were identified, reflecting the diversity and richness of research in this field. The thematic evolution showed interesting changes in focus topics over time, highlighting the intersection of microplastics with topics such as “covid‐19” and “public health.” Conclusions These findings underscore the relevance and urgency of microplastic and public health research and suggest promising directions for future research. The increasing volume of published research in these fields over time reflects the continuing importance of microplastics research and its impact on public health.